Acute interstitial pneumonia in feedlot cattle - Valles, Jose Antonio (Kansas State University, 2013)
Acute Interstitial Pneumonia (AIP) is a costly issue that affects feedlot cattle, especially during hot and dry summers. Research has yet to elucidate the exact etiology of AIP; therefore this study was conducted to determine possible factors that contribute to AIP in feedlot cattle. During the summer of 2011 in a 55,000 head feedyard in southwest Kansas, animals exhibiting clinical signs of AIP were selected for ante-mortem examination and data collection. The animal population within the feedlot consisted of 75% heifers and 25% steers. Approximately 50% of the animal population was black hided animals. Ante-mortem data consisted of rumen gas cap measurement for NH3 and H2S, rumen pH, serum chemistry, rectal temperature, and body weight. Post-mortem cases with and without ante-mortem evaluations were also selected for an additional examination. Postmortem examination included similar data as ante-mortem examination with addition of visual and histological examination of lung tissue. There were 31 ante-mortem cases of clinical AIP with the following observations (mean ± SD): rectal temperature 105.3 ± 0.7 °F, weight 1098 ± 123 lbs., H2S 136 ± 133.3 ppm, and rumen pH 6.4 ± 0.5. Twenty-five healthy cohorts were selected from identical pens to serve as controls. Observations from control animals were: rectal temperature 103.7 ± 1.1 °F, weight 1113 ± 133.3lbs, H2S 269.8 ± 311.6 ppm and rumen pH 6.2 ± 0.6. A total of 61 post-mortem cases with a preliminary diagnosis of AIP were analyzed and displayed the following values: H2S 1279.7 ± 1569 ppm, and rumen pH 6.3 ± 0.36. Fifty-three of these postmortem cases had diffuse, focal and /or patchy AIP confirmed by histology.
Keywords: Acute interstitial pneumonia; AIP; Beef cattle; Feedlot; Veterinary Medicine (0778)